RESPIRATORY TRACT BACTERIAL INFECTION ETIOLOGICAL AGENTS AND SUSCEPTIBILITY TESTING - Faris, Nawal. S. (European Scientific Journal, ESJ, 2014)
Respiratory tract infections are believed to be one of the main reasons peoplestill visits their GP or pharmacist.Respiratory tract infections (RTIs) are the leading cause of Death in USA. Thus, lower respiratory tract infections(LRIs) are generally more serious than upper respiratory infections. Specifically, the LRIs have been themajor cause of death among all infectious diseases. However, the two most common LRIs are bronchitis and pneumonia. Typical infections of the upper respiratory tract include tonsillitis, pharyngitis, laryngitis, sinusitisandotitis media. The aim of this study is to strengthen the surveys of the cases and the causes of therespiratory tract infection. This study also aims at evaluating the number of persons whohad negative result and the reason for the lack of screening of all pathogenic virus and search for bacterial infection only. In addition,this study finally carries out culture characterization and antibiotic susceptibility testing of the isolated pathogenic bacteria. In order to attain these goals, we carried out a survey of 635 throat swabsand sputum sample between January 2013 to December 2014 using throat and sputumin the Department of Microbiology at the Central Laboratory ofthe Ministry of Health in Ammanthe capital of Jordan. In addition, culture and biochemical test and antiserawere also carried out. Atotal of 635individuals (275 males and 360 females)swabs and sputumwere tested for bacterial infection, a total 55 throat swabs showed positive results for Group A beta-hemolytic streptococci with an overall prevalence of 8.7 %.Also, a total of 23 sputum samplesshowed positive results for different types of bacterial infection with an overall prevalence of 10 %. After then, the result about their antibiotic susceptibility was reported. In conclusions, Group A beta-hemolytic streptococci isthe most common cause of the upper respiratory tract infection, whileK. pneumoniais the most common cause of lower respiratory tract infection.